CULTURE OF LITERACY BASED ON A SCIENTIFIC APPROACH TO HUMAN DIGESTIVE SYSTEM MATERIALS - Yohana Fransiska; Jonner Nainggolan; Hotlan Samosir (Jurnal Ilmu Pendidikan Indonesia, 2023)
The research aims to determine literacy culture based on a scientific approach to the material of the human digestive system. Formative evaluation research method. The research sample was class V SD YPPGI Sentani with a total of 23 students. The results showed that literacy culture based on a scientific approach to the material of the human digestive system can improve student learning outcomes with an average n-gain of 0.6 in the medium category